2014
DOI: 10.33687/phytopath.003.03.0284
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition, Antimicrobial Effect of Azadirachta indica and Carica papaya Extracts on Fungi Isolated From Gmelina arborea Seedling

Abstract: Gmelina arborea Roxb has important economic value in Nigeria and worldwide. It has been used as timber, for pulp and paper, furniture, plywood and for particle board. Due to the menace caused by fungal diseases in nurseries and sites where the seedlings are raised and the observed disease severity at the Awi Gmelina Forestry Project Nursery in Cross River State, Nigeria. It became necessary to provide a viable environmentally friendly measure to curb the diseases, hence, a trial on the antifungal effects of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In this study, methanolic A. indica extract demonstrated an inhibitory effect against pancreatic cholesterol esterase activity similar to a previous in vitro study where polyphenols present in grape seed inhibited pancreatic cholesterol esterase (15). Another study, using phytochemical screening, showed A. indica contains secondary metabolites such as alkaloids, glycosides, flavonoids, and polyphenols (27). Moreover, the methanolic A. indica seed oil extracts also revealed the presence of saponins, terpenes, tannins and steroids (1828).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, methanolic A. indica extract demonstrated an inhibitory effect against pancreatic cholesterol esterase activity similar to a previous in vitro study where polyphenols present in grape seed inhibited pancreatic cholesterol esterase (15). Another study, using phytochemical screening, showed A. indica contains secondary metabolites such as alkaloids, glycosides, flavonoids, and polyphenols (27). Moreover, the methanolic A. indica seed oil extracts also revealed the presence of saponins, terpenes, tannins and steroids (1828).…”
Section: Discussionmentioning
confidence: 99%